Pengaruh Intellectual Capital terhadap Kinerja Perbankan Umum Konvensional di Indonesia - Nanda , Annisa; Kemas M. Husni Thamrin; Fida Muthia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Banking is the lifeblood of the economy throughout the country, many wheels of the economy are mainly driven by banks either directly or indirectly. Banking in Indonesia plays a very important role, moreover Indonesia is a developing country in all sectors. This study aims to analyze the effect of banking performance on profitability at conventional commercial banks in Indonesia during the 2018-2022 period. The data used in this study were obtained from the Indonesia Stock Exchange (IDX) with a sample of 16 conventional commercial banks and used panel data regression analysis techniques. The results of the analysis show that Value Added Capital Employed (VACA) has a positive and significant effect on Return on Assets (ROA) and Value Added Human Capital (VAHU) has a negative and significant effect on ROA. However, the Structural Capital Value Added (STVA) variable has no significant effect on ROA at 16 conventional commercial banks in Indonesia during the study period.